Process improvement of a restaurant through the implementation of an information system - Casas Huamanta, Edwin Roi (SATHIRI, 2021)
This research aimed to improve the sales process and customer service based on the needs of a restaurant, making use of information and communication technologies, in this case with the implementation of a web environment information system and application for devices with Android operating system that allows you to effectively and efficiently manage delivery orders, as well as orders from diners at your service location; Likewise, the information system serves as support for decision-making regarding the dishes to be prepared according to the dates based on the preferences of the customers. Two study variables were established; sales and customer service; each with its study dimensions to measure the improvement of the processes. The research was of an applied type, has a quantitative approach and is pre-experimental because an instrument or test was applied before and after implementing the system, the technique to collect the information was the survey and the instruments were two questionnaires, one for each variable study, which measure the level of effectiveness in sales and the level of satisfaction in customer service. As a result, it was obtained that the implementation of the information system improves the restaurant’s sales and customer service process in a highly significant way. Concluding that the implementation of the system improved sales management and customer service.
Keywords: Information system; process automation; sales; customer service; restaurant